2004
DOI: 10.5038/2375-0901.7.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Transit Price Elasticities and Cross - Elasticities

Abstract: This paper summarizes price elasticities and cross elasticities for use in public transit planning. It describes how elasticities are used, and summarizes previous research on transit elasticities. Commonly used transit elasticity values are largely based on studies of short-and medium-run impacts performed decades ago when real incomes where lower and a larger portion of the population was transit dependent. As a result, they tend to be lower than appropriate to model long-run impacts. Analysis based on these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
2
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(175 citation statements)
references
References 8 publications
4
147
2
8
Order By: Relevance
“…In addition, the authors offer only the principle of the calculation, not a specific methodology. Litman (2004), Nagendra (2012), Dodlova (2013) and others consider taking into account the demand elasticity for passenger transport by price is necessary for developing an optimal tariff policy. This approach of tariff determining based on a research of passenger demand and modelling passenger response to price changes.…”
Section: Literature and Research Reviewsmentioning
confidence: 99%
“…In addition, the authors offer only the principle of the calculation, not a specific methodology. Litman (2004), Nagendra (2012), Dodlova (2013) and others consider taking into account the demand elasticity for passenger transport by price is necessary for developing an optimal tariff policy. This approach of tariff determining based on a research of passenger demand and modelling passenger response to price changes.…”
Section: Literature and Research Reviewsmentioning
confidence: 99%
“…In Spain, local and regional authorities fi nance more than 80% of the resources in the largest cities, while the rest is provided by the national government. [3], [4] In Poland, local authorities fi nance 100% of the resources and differences between main activity incomes and costs of the system functioning.…”
Section: The Structure Of Incomes In Public Transit System In the Chomentioning
confidence: 99%
“…Litman [19] summarized price elasticity in public transit planning and concluded that elasticity was affected by user type, trip type, geography, type and direction of price change, time period, and transit mode. The elasticity of transit ridership with respect to fares was usually within a range of À0.2 to À0.5 in the short run (first year), and increased to À0.6 to À0.9 over the long run (5-10 years).…”
Section: Literature Reviewmentioning
confidence: 99%